Restaurateurs and diners responsiveness toward smart card usage in restaurants / Zurena @ Rena Shahril - Shahril, Zurena @ Rena (Institute of Graduate Studies, UiTM, 2017)
With the general thrust of developments and in line with technological advancement and demands of the economy, the payment systems have gone through incredible revolutions. This scenario is offering greater competence and expediency to customers and businesses and the growth in technology without an exception of food and beverage industry has played a vital role in changing diners’ payment habits. The availability range of payment services in the restaurants today including the smart card in response to diverse market demands of the changing behaviour and lifestyle of the diners significantly influence their actual usage behaviour. Nevertheless, although smart cards are viewed as a promising and enabling technology, their levels of acceptance and usage have not been at its peak in the Malaysian restaurant industry. This study is empirically investigating restaurateurs and diners responsiveness toward “Touch ‘n Go” smart card usage in Malaysian restaurant sector. In integrating, entwining the issues or to facilitate the research problems and the findings both quantitative and qualitative approaches were opted. The insight on the issues was obtained through the interview with 6 restauranteurs while the deeper understanding is validated through self-administered survey among the 400 restaurant diners. With the various statistical analyses ranging from descriptive, inferential and SEM Partial Least Square used to answer the research objectives, questions and hypotheses, some useful insights pertaining to the issues investigated was significantly obtained…